Implementasi Fuzzy Time Series Chen untuk Prediksi Jumlah Mahasiswa Baru Universitas Tidar - Nur Khanifah; Intan Fadhila; Rahmat Aldino; Piyadhammo Jansen Conggono (Program Studi Teknik Elektro Universitas Khairun, 2022)
Higher education becomes a level of further education after pursuing a secondary education program. Tidar University is one of the public higher education institutions located in Central Java Province. Since its inception in 1979, Tidar University has only undergone a change in status to a public university in 2014. This change has an influence on the increase in the number of enthusiasts who want to study at Tidar University. In addition, there were several new study programs at Tidar University in different years which also led to an increase in the number of new students of Tidar University. However, the Covid-19 pandemic also brought an influence that led to a drastic decrease in the number of enthusiasts at Tidar University. This study tried to implement chen's fuzzy time series to predict the number of enthusiasts in the first 10 study programs of Tidar University. In this prediction process, the number of intervals used affects the forecasting results. To determine the number of intervals, the Sturges formula is used. The prediction results showed the smallest MAPE value of 5.7551% in the agrotechnology study program and the largest MAPE at 28.3936% in the accounting D3 study program